Chelation-assisted assembly of multidentate colloidal nanoparticles into metal–organic nanoparticles. Issue 45 (14th November 2018) - Liu, Yuan; Sun, Hao; Yang, Lu; Zhu, Xiaochen; Wang, Xirui; Liang, Jiamin; Li, Xiaowei; Jiang, Ying; Hou, Weijia; Favero Ferreira, Caue; Talham, Daniel R.; Hebard, Arthur F.; et al.
Abstract : We propose a chelation-assisted assembly of multidentate CNs into metal–organic nanoparticles (MONs). Abstract : We propose a chelation-assisted assembly of multidentate CNs into metal–organic nanoparticles (MONs). Multidentate CNs functionalized with coordination sites participate equally as organic linkers in MON construction, which is driven by chelation between metal ions and coordination sites. MONs assembled from Au nanoparticles display particle number- and size-dependent optical properties. In addition, the resulting CN-assembled MONs give evidence that assembly was dictated by the multidentate surface ligand rather than the size, shape or material of CNs. With this chelation-assisted strategy, it is possible to control the number of assembled CNs and build the connections between them.